ALKALI TREATMENT OF FAN PALM NATURAL FIBERS FOR USE IN FIBER REINFORCED CONCRETE - Machaka, Meheddene; Basha, Hisham; Abou Chakra, Hadi; Elkordi, Adel (European Scientific Journal, ESJ, 2014)
It is well known that the addition of fibers to concrete mix enhancesits performance. There are many types of fibers in the market, but forenvironmental protection purposes, the use of natural fibers rather thansynthetic fibers is highly recommended. However, natural fibers are affectedby the presence of Alkali environment of concrete; however, treating fiberswith chemical solution reduces the effect of Alkali attack and overcomes theweak bond between the fiber and the cement matrix by formation of a roughfiber surface. Alkali treatment is one of the most used methods for treatmentof natural fibers. In this study various Alkali treatment procedures on FanPalm fibers have been used to define the optimum procedure that enhancesthe durability of Fan Palm natural fiber in concrete without causing seriousdeterioration to the fiber itself. For that, an experimental program wasconducted to study the effect of different treatment procedures on the tensilestrength of fibers, modulus of elasticity, and the elongation of fibers at break.Thus, the treatment was applied at various concentrations of SodiumHydroxide solutions (1%, 2%, 4%, & 10%) and treatment durations (2 hrs , 8hrs, & 24 hrs ). From the tested fibers, the maximum tensile forces at breakand elongations were recorded. From the analysis of test results it wasconducted that using 4% sodium hydroxide concentration for 24 hours wasthe preferred treatment procedure for Fan Palm fibers.